2011
DOI: 10.2134/jeq2010.0179
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Lysimeter Studies of Glyphosate and Aminomethylphosphonic Acid in a Sand and a Clay Soil

Abstract: Due to the increasing concern about the appearance of glyphosate [N-(phosphonomethyl)glycine] and its major metabolite aminomethylphosphonic acid (AMPA) in natural waters, batch laboratory and lysimeter transport studies were performed to assess the potential for leaching of the compounds in two agricultural soils. Unlabeled and 14 C-labeled glyphosate were added at a rate corresponding to 1.54 kg a.i. ha −1 on undisturbed sand and clay columns. Leachate was sampled weekly during a period of 748 d for analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
113
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 37 publications
18
113
1
4
Order By: Relevance
“…Leaching of DRP (concentrations and load) was significantly lower from the Mellby sand than from the Nåntuna sand (P < 0.01) despite considerably higher Olsen P content in the Mellby sand topsoil (Table 1) and small amounts of preferential flow in both soils Bergström et al, 2011). Considerably higher sorption capacity in the Mellby sand subsoil due to the presence of Fe-oxides (Table 1) efficiently functioned as a sink for P leaching.…”
Section: Comparison Of P Leaching From Full-length and Subsoil Profilesmentioning
confidence: 97%
“…Leaching of DRP (concentrations and load) was significantly lower from the Mellby sand than from the Nåntuna sand (P < 0.01) despite considerably higher Olsen P content in the Mellby sand topsoil (Table 1) and small amounts of preferential flow in both soils Bergström et al, 2011). Considerably higher sorption capacity in the Mellby sand subsoil due to the presence of Fe-oxides (Table 1) efficiently functioned as a sink for P leaching.…”
Section: Comparison Of P Leaching From Full-length and Subsoil Profilesmentioning
confidence: 97%
“…kGPxo Rate constant of oxidized GPx with GSH to form intermediate GSGPx [40] kGSSG Rate constant of GSGPx with GSH to recycle reduced Gpx [40] kGR Rate constant for molecular GR activity [34] KGR MichaelisMenten constant of GR for GSSG [34] KGRN MichaelisMenten constant of GR for NADPH [34] kNAP Rate constant for the conversion of NADP to NADPH [34] VCPLG Conversion of glyphosate to sarcosine [41] Kglypexud Extrudation of Glyphosate [42] KCPLG MichaelisMenten constant for the conversion of glyphosate to sarcosine [41] KSOX Catalytic rate constant for the conversion of sarcosine to glycine [43] kSOX MichaelisMenten constant for the conversion of sarcosine to glycine [43] KmGO MichaelisMenten constant for the conversion of glyphosate to AMPA [24] kGO Catalytic rate constant for the conversion of of glyphosate to AMPA [24] kAMPA Rate constant for the conversion of AMPA to methylamine [44] VMDH Maximal production of formaldehyde from methylamine [45] KMDH MichaelisMenten constant for the formation of formaldehyde from methylamine [45] Submit or recommend next manuscript to SCIRP and we will provide best service for you:…”
Section: Appendix Bmentioning
confidence: 99%
“…Agricultural land in the prairies is more prone to wind erosion than agricultural land in other regions of Canada, and wind erosion and atmospheric particulate transport occurs particularly in drier years (Coote et al 1981, Lobb et al 2010. Following agricultural application, most glyphosate residues are retained in the soil surface layer due to its strong sorption by soil (AlRajab et al 2008, Bergström et al 2011) and hence glyphosate is prone to be transported by wind-eroded sediments. For herbicides applied to the soil surface at a Prairie agricultural site, Larney et al (1999) demonstrated that on average 4.5% of that applied could be detected in eroded sediment.…”
Section: Resultsmentioning
confidence: 99%